East Asian Transwar Popular Culture
XIV, 304 p. 19 illus.
Keywords: This collection examines literature and film studies from the late colonial and early postcolonial periods in Taiwan and Korea, and highlights the similarities and differences of Taiwanese and Korean popular culture by focusing on the representation of gender, genre, state regulation, and spectatorship. Calling for the “de-colonializing” and “de–Cold Warring” of the two ex-colonies and anticommunist allies, the book places Taiwan and Korea side by side in a “trans-war” frame. Considering Taiwan–Korea relations along a new trans-war axis, the book focuses on the continuities between the late colonial period’s Asia-Pacific War and the consequent Korean War and the ongoing conflict between the two sides of the Taiwan Strait, facilitated by Cold War power struggles. The collection also invites a meaningful transcolonial reconsideration of East Asian cultural and literary flows, beyond the conventional colonizer/colonized dichotomy and ideological antagonism.